2022
DOI: 10.3390/jcm11102736
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 Vaccination Cause Storage Lower Urinary Tract Symptoms?

Abstract: We investigated the storage lower urinary tract symptoms (LUTS) before and after the first dose of coronavirus disease 2019 (COVID-19) vaccine and the association between pre-vaccinated overactive bladder (OAB) and the worsening of storage LUTS following COVID-19 vaccination. This cross-sectional study in a third-level hospital in Taiwan used the validated pre- and post-vaccinated Overactive Bladder Symptom Score (OABSS). Diagnosis of OAB was made using pre-vaccinated OABSS. The deterioration of storage LUTS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…23 In line with prior literature, we found that it is not likely that the COVID-19 immunization is associated with LUTS as no adverse event within that category produced a positive signal, other than a potential overreporting of bladder spasm in Janssen vaccinations. 17 This evidence is potentiated by a previous study evaluating adverse urologic events associated with COVID-19 vaccination in 341 medical students across Jordan, which found no significant increase in the number of students with LUTS following COVID-19 immunization. 24 Data mining of the VAERS database has several limitations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…23 In line with prior literature, we found that it is not likely that the COVID-19 immunization is associated with LUTS as no adverse event within that category produced a positive signal, other than a potential overreporting of bladder spasm in Janssen vaccinations. 17 This evidence is potentiated by a previous study evaluating adverse urologic events associated with COVID-19 vaccination in 341 medical students across Jordan, which found no significant increase in the number of students with LUTS following COVID-19 immunization. 24 Data mining of the VAERS database has several limitations.…”
Section: Discussionmentioning
confidence: 94%
“…16 Similarly, though it has been demonstrated that overactive bladder (OAB) patients were more likely to report LUTS following COVID-19 immunization compared to non-OAB patients, neither OAB patients nor non-OAB patients reported statistically significant increases in the validated Chinese OAB symptom score following COVID-19 immunization. 17 Interestingly, a small Japanese study performed by Matsuzaki et al found new-onset or worsening hematuria following COVID-19 vaccination in 14 individuals, 8 (57.1%) of whom had previously diagnosed IgA nephropathy. 18 However, there are few large-volume studies examining urologic side effects of the coronavirus vaccine such as the present analysis.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that this difference in age may have contributed to differences in reported symptoms 18 . COVID‐19 infection and the COVID‐19 vaccine have more recently been shown to increase inflammation in the lungs and elsewhere 14,19 . Though we did not collect information on individual COVID‐19 infection and vaccination status, it is possible that this could have contributed to IC/BPS symptomology.…”
Section: Discussionmentioning
confidence: 99%
“…18 COVID-19 infection and the COVID-19 vaccine have more recently been shown to increase inflammation in the lungs and elsewhere. 14,19 Though we did not collect information on individual COVID-19 infection and vaccination status, it is possible that this could have contributed to IC/BPS symptomology. Similarly, three in the pre-pandemic and six during the pandemic opted for cystoscopy with hydrodistension for treatment of an initial IC/BPS flare.…”
Section: It Is Possible That Patients Who Had a Known Diagnosis Of Ic...mentioning
confidence: 99%
“…Self-reported adverse effects following COVID-19 vaccination have been described in several studies with mRNA-based (Moderna and Pfizer-BioNTech) and viral vector (AstraZenko) vaccines, the most common being localized symptoms at the first dose, such as pain at the injection site, and systemic symptomatology such as weakness, headache, fever, chills and fatigue at the second dose (7,8). Several studies report an increase in lower urinary tract urological symptomatology such as increased frequency and urgency of urination (9)(10)(11). Such is the case of research published on 889 subjects where lower urinary tract and overactive bladder symptomatology was studied before and after vaccination.…”
Section: Introductionmentioning
confidence: 99%